2018
DOI: 10.1017/s0025100318000117
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic properties of formality in conversational Japanese

Abstract: This paper examines potential prosodic cues for level of formality in Japanese conversational speech using speech data gathered via one-on-one interviews. Based on previous work on the phonetic properties of formality in Japanese (Ofuka et al. 2000, Ito 2002), further studies of Korean (Winter & Grawunder 2012) and Catalan Spanish (Hübscher, Borràs-Comes & Prieto 2017), and on a lab-based pilot study, the study examined properties of f0, intensity, pause frequency, and articulation rate via mixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A look at table 1 makes it apparent that the correlates of polite speech are quite variegated, sometimes even when it comes to different studies of the same language. For example, for Japanese, there is evidence that is consistent with the idea that high pitch signals politeness [36,56,92], as well as studies that found a lowering of pitch [104], as well as studies that found no reliable differences [103]. However, one issue that makes it hard to establish any overarching cross-linguistic tendencies is that the studies used different tasks, as well as different definitions of politeness.…”
Section: The Frequency Codementioning
confidence: 93%
See 1 more Smart Citation
“…A look at table 1 makes it apparent that the correlates of polite speech are quite variegated, sometimes even when it comes to different studies of the same language. For example, for Japanese, there is evidence that is consistent with the idea that high pitch signals politeness [36,56,92], as well as studies that found a lowering of pitch [104], as well as studies that found no reliable differences [103]. However, one issue that makes it hard to establish any overarching cross-linguistic tendencies is that the studies used different tasks, as well as different definitions of politeness.…”
Section: The Frequency Codementioning
confidence: 93%
“…Table 1 shows that there are a number of studies that can be thought of as contradicting the frequency code. These studies either find that speakers actively lower their voice pitch in a polite condition as opposed to a comparison condition [87,97,100,101,104,106,107] or they find no consistent pitch difference [103,105]. A look at table 1 makes it apparent that the correlates of polite speech are quite variegated, sometimes even when it comes to different studies of the same language.…”
Section: The Frequency Codementioning
confidence: 99%
“…Methodological differences may be of help in explaining the discrepancy between the current work and the previous literature: Ohara (1999) analyzed spontaneous speech, whereas we analyzed read speech. In Japanese, politeness is marked lexically, grammatically and phonetically ( Sherr-Ziarko, 2019 ). It may be that in the present study, where participants could only manipulate the phonetic dimension of their speech, as it is a reading task, males did not hesitate to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The utterances in that study were much shorter, simpler, lab-elicited sentences, for which third-order polynomials were sufficient. Sherr-Ziarko (2019) used 25th-order polynomials (!) to first fit and then segment f 0 contours in long Japanese utterances containing many pitch accents.…”
Section: Notesmentioning
confidence: 99%